2011
DOI: 10.1108/15265941111158505
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the capital‐structure puzzle: UK evidence

Abstract: We explore the potential drivers of corporate capital-structure decision. We apply both fixed effects panel models and random effects tobit models to examine this issue. Based on a sample of 379 firms across the period from 1991 to 2002, we find that corporate characteristics (firm size, firm risk, firm growth rate, firm profitability and asset tangibility) and corporate governance characteristics (board size and outside directorships) are the main drivers of capital-structure of UK firms. In addition, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 27 publications
7
50
0
Order By: Relevance
“…To compare with previous studies, the internal corporate governance variable represented in the institutional investors only has a statistically significant correlation with capital structure decisions in UAE firms (Hussainey, K. and Al-Najjar, B. , 2011b). The institutional investors has statistically insignificant correlation with short term debt finance indicating that Egyptian firms rely more on short term debt finance due to instability of economy growth resulting in the shortage of funds.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To compare with previous studies, the internal corporate governance variable represented in the institutional investors only has a statistically significant correlation with capital structure decisions in UAE firms (Hussainey, K. and Al-Najjar, B. , 2011b). The institutional investors has statistically insignificant correlation with short term debt finance indicating that Egyptian firms rely more on short term debt finance due to instability of economy growth resulting in the shortage of funds.…”
Section: Resultsmentioning
confidence: 96%
“…Early research by Miller and Modigliani, (1958) is the primary research to look at the relevance of capital structure decisions in an efficient capital market. Not only that but also to investigate the determinants of capital structure decisions (Al-Najjar, B. and Hussainey, K., 2011b). The substance of executing corporate governance practices is significant for the growth of any company and the development to any economy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, prior research finds that large firms are more likely to finance their activities using debt than smaller firms (Al-Najjar and Hussainey, 2009a and2009b). Finally, prior research found a negative relationship between dividend policy and capital structure.…”
Section: Methodsmentioning
confidence: 98%
“…Despite the extensive research done in the area of capital structure since Modigliani andMiller in 1958 andever since Myers (1977) published his article on the determinants of corporate borrowing, understanding in the area is still inconclusive (Harris & Raviv, 1991;Gill et al, 2009;Sheikh & Wang, 2011;Al-Najjar & Hussainey, 2011;Gwatidzo & Ramjee, 2012). Empirical work in this area, according to Titman and Wessels (1988), has lagged behind the theoretical research.…”
Section: Notes 1 Introductionmentioning
confidence: 96%